Requirements for Presidential and Vice Presidential Candidates Based on Law Number 7 of 2017 Concerning Elections from a Fiqh Siyasah Perspective - Umah, Vina Khoerul (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
This study examines the requirements for presidential and vice-presidential candidates as stipulated in Law No. 7 of 2017 on General Elections using the perspective of Fikih Siyasah. This study is motivated by the dynamics of election law in Indonesia, particularly regarding the formulation of national leadership qualifications that are not only administrative in nature but also rich in moral and ethical dimensions of leadership. This research is a normative legal study with a conceptual and legislative approach, using a literature review method of primary, secondary, and tertiary legal sources. The results of the study show that the provisions on the requirements for presidential and vice-presidential candidates in Article 169 of Law No. 7 of 2017 basically reflect the basic principles of Fikih Siyasah, especially those related to integrity, capability (kifāyah), physical and mental health, and commitment to the values of justice and public interest. However, there are several leadership criteria in Fikih Siyasah such as certain aspects of religiosity and more substantive moral-spiritual qualities that are not explicitly regulated in positive law. Therefore, this study emphasizes that national election law and Fikih Siyasah have a complementary relationship, in which Islamic values can serve as an ethical foundation for the improvement of democratic leadership regulations in Indonesia.